EDUCATION OF YOUTH IN THE SPIRIT OF PATRIOTISM - Karshiyev Azamat Rakhmonovich (Journals Park Publishing, 2022)
In recent years, certain works have been carried out in our country in the field of military-technical training of graduates, in the development of intellectually mature and physically healthy individuals, favorable conditions for sports, including its technical and practical types was created. The article explores extracurricular activities in educating young people in the spirit of military patriotism.
Keywords: patriotism, spirits, education of youth, motherland, knowledge